ANALYSIS OF JERNANG FARMING BUSINESS (Daemonorops draco) IN PAYA KOLAK VILLAGE, CELALA DISTRICT, CENTRAL ACEH REGENCY: ANALISIS USAHA TANI JERNANG (Daemonorops draco) DI DESA PAYA KOLAK KECAMATAN CELALA KABUPATEN ACEH TENGAH - Fitri; Desparita, Naya; Elfiana (Universitas Veteran Bangun Nusantara, 2025)
This study aims to determine the benefits and feasibility of Mr Sabri's Jernang (Daemonorops draco) farming business. This research was conducted in Paya Kolak Village, Celala District, Central Aceh Regency, which was carried out in November 2024. The data analysis method in this study uses a quantitative method using the formula for analyzing total costs, revenues, profits, Break Even Point (BEP) analysis, Revenue Cost Ratio (R / C), Benefit Cost Ratio (B / C), NVP (Net Present Value) and IRR (Internal Rate Of Return). Based on the results of the research and analysis that have been carried out, with a total profit of Rp. 4,277,248.1, -, while the total cost is Rp. 1,977,248.1 / month, consisting of fixed depreciation costs of Rp. 122,048.1, - / month and variable costs of Rp. 1,855,200 per month. From the BEP calculation, the BEP production value is 39.54/kg, and the BEP price is Rp. 19,722,481/kg, the R/C ratio is 1.11, the B/C ratio value is 2.11, and the NPV amount is Rp. 18,196,364, - and the percentage obtained in finding the IRR is 85%, so it can be concluded that the jenang farming business in Paya Kolak Village, Celala District, Central Aceh Regency is profitable and feasible to develop.